1992
DOI: 10.1007/bf02049397
|View full text |Cite
|
Sign up to set email alerts
|

Respective roles of radiotherapy and surgery in the management of epidermoid carcinoma of the anal margin

Abstract: The study of 54 patients treated curatively by irradiation with or without surgery is reported. The crude and cancer-specific five-year survival rates are 59.2 percent and 79.7 percent. Three patients were treated palliatively. The great variation in histologic type, clinical appearance, disease stage, and patient status justifies the definition of a treatment strategy using radiotherapy, surgery, or a combination of the two methods. T1 and T2 squamous- or basal-cell carcinomas are suitable for local excision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 13 publications
1
55
0
2
Order By: Relevance
“…The acute radiation-related damage of the tissues is increased when chemotherapeutic drugs are associated [20,21]. Late complications (sphincterial tone alterations with reduced anal continence, persistent anal ulcer, rectovaginal or entero-enteric fistulae, skin sclerosis, necrosis, and organ damage) have been reported in 6%-14% of the patients [5,6,13,15,16,[21][22][23][24][25][26][27]. Complications related to the radiation treatment of inguinal lymphatic metastases (femoral head or neck fractures, leg lymphedema) have been reported as well (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The acute radiation-related damage of the tissues is increased when chemotherapeutic drugs are associated [20,21]. Late complications (sphincterial tone alterations with reduced anal continence, persistent anal ulcer, rectovaginal or entero-enteric fistulae, skin sclerosis, necrosis, and organ damage) have been reported in 6%-14% of the patients [5,6,13,15,16,[21][22][23][24][25][26][27]. Complications related to the radiation treatment of inguinal lymphatic metastases (femoral head or neck fractures, leg lymphedema) have been reported as well (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the lack of statistical significance for overall survival and CFS in our analysis. Other authors also found tumor site at the anal margin to be associated with inferior prognosis [32][33][34]. The reason for the inferior prognosis of tumors at the anal margin is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have observed a slight female predominance while others report an equal or male predominant distribution [5,[7][8][9][10][11]. Presenting symptoms include pain, bleeding, palpable mass, change in bowel habits, hemorrhoids, discharge, and weight loss [4,5].…”
Section: Introductionmentioning
confidence: 99%